Farmer preferences and market vaues of cattle breeds of west and central Africa - Jabbar, M.A.; Swallow, B.M.; D'Ieteren, G.D.M.; Busari, A.A. (International Livestock Research Institute, 1999)
World agriculture is based on a small number of animal species and a decreasing number of breeds within each species. Several breeds of West African shorthorn cattle (Bos taurus brachyceros) are now at high risk of extinction due to interbreeding. The West African shorthorn breeds are particularly important resources because of their superior abilities to resist diseases, particularly trypanosomosis, and be productive under high humidity, heat stress, water restriction and with poor quality feed. A study was undertaken in the derived savanna area of southwest Nigeria to determine the prospects for conservation through use and possible improvement of the Muturu, a West African shorthorn breed known to be in decline throughout southern Nigeria. An analysis of farmers' breeding practices and breed preferences confirmed a strong trend away from Muturu and identified the traits farmers find least desirable about the Muturu relative to other breeds. An analysis of cattle market prices found small, but significant, price differences by breed. The best hopes for increased utilization likely in other areas of West Africa, such as southeast Nigeria, where the Muturu is better suited to the farming systems and there is a large market for this breed.